Good Health, Quality Education, Sustainable Communities, Human Rights The scientific contribution of Italian UNESCO Chairs and partners to SDGs 2030 - baños, josep-e; Orefice, Carlo; BIANCHI, FRANCESCA; COSTANTINI, STEFANO (Strumenti per la didattica e la ricerca, 2019)
The publication collects the contributions presented during the International Symposium of the Italian UNESCO Chairs (CONIUS) entitled Human Rights and Sustainable Development Goals 2030, which took place on 16 November 2018 at the University of Florence. The contributions of national and international experts address the Global Aims for Sustainable Development of the UNESCO including Sustainable Development Goals (SDGs) n. 3 Improvement of the 'Global Health', n. 4 'Quality Education', n. 11 'Cities and Inclusive Human Sett lements' and n. 16 'Peace and Justice', using transdisciplinary and transnational perspectives and implemented through theoretical studies and good practices.